Family Background and Child Health - Yeon Soo Kim (Korea Development Institute (KDI), 2012)
Socioeconomic inequity in health is of concern in many developed countries. In Korea, authorities have started to recognize the need to address this issue, as evidence on its adverse consequences grew. Health inequity in children receives particular interest because of its potential long-run implications on adult outcomes such as educational attainment and labor market success. Disadvantages occurring at this early stage may be hard to mediate and costly to reverse. This study is an investigation into the relationship between child health and family background using nationally representative data from the Korean National Health and Nutrition Examination Survey. It confirms the existence of a socioeconomic gradient in child health, examines the role of nutrition and diet-related factors, and provides an evaluation on the income-related inequity in the distribution of health care utilization.
Keywords: 330